2015 IEEE Tenth International Conference on Intelligent Sensors, Sensor Networks and Information Processing (ISSNIP) 2015
DOI: 10.1109/issnip.2015.7106927
|View full text |Cite
|
Sign up to set email alerts
|

A new query processing model for maintaining data temporal consistency in Wireless Sensor Networks

Abstract: Maintaining data temporal consistency in a Wire less Sensor Network (WSN) has attracted the attention of many researchers. Nowadays, there are many applications based on WSN which require consistent and valid measures to reflect the current state of the environment being monitored, or to quickly respond to some critical situations. In this paper, we propose a new query processing mechanism, giving each node the possibility to control the temporal validity of data in order to reduce the amount of invalid data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The simulation results and the comparison with other state-ofthe-art methods have shown that our routing protocol balances the routing load, increases the network lifetime, and reduces energy consumption. Authors in [8] introduce a query processing method to improve the amount of valid data transmitted in the network. Firstly, they run some verifications using network connectivity and synchronization (among nodes) before injecting any query in the network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results and the comparison with other state-ofthe-art methods have shown that our routing protocol balances the routing load, increases the network lifetime, and reduces energy consumption. Authors in [8] introduce a query processing method to improve the amount of valid data transmitted in the network. Firstly, they run some verifications using network connectivity and synchronization (among nodes) before injecting any query in the network.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in developing query-driven applications in WSN [3], attribute-based naming is necessary to specify the properties of data in a query. However, there is no standard naming scheme for various complex applications in the literature, which limits the deployment of the data-centric approaches in practice for WSNs [4][5][6][7][8][9]. In the meantime, named data networking (NDN) has emerged as a promising field to cope with the usage of today's internet which follows data-centric communication [10] [11].…”
Section: Introductionmentioning
confidence: 99%